2016
DOI: 10.26491/mhwm/62256
|View full text |Cite
|
Sign up to set email alerts
|

The importance of hourly nutrient concentration variability in terms of assessment of the surface water state in Słupia pilot river

Abstract: Water eutrophication still causes many environmental and social problems, and so better quantification of the amount of nutrient loads discharged into surface waters is required. The basis for eutrophication analysis is data gathered in the frame of State environmental Monitoring (SeM). in Poland, these measurements are carried out at the frequency of 6-12 times per year and serve as the basis for calculating the amount of nutrient input discharged to the sea. This article presents the results of the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The aforementioned research conducted also at the neighbouring catchments confirmed that the Słupia River may be considered a representative catchment for the whole Pomeranian region. Therefore, it plays an important role in the estimation of TN loads from the territory of Poland into the Baltic Sea [38][39][40]. The Słupia River has a length of 139 km, and its catchment covers an area of 1623 km 2 .…”
Section: Modeling Of Nvz Revision' Impact-variant Scenariosmentioning
confidence: 99%
“…The aforementioned research conducted also at the neighbouring catchments confirmed that the Słupia River may be considered a representative catchment for the whole Pomeranian region. Therefore, it plays an important role in the estimation of TN loads from the territory of Poland into the Baltic Sea [38][39][40]. The Słupia River has a length of 139 km, and its catchment covers an area of 1623 km 2 .…”
Section: Modeling Of Nvz Revision' Impact-variant Scenariosmentioning
confidence: 99%